Simultaneous Relationship Between Competence and Burn Out to Patient Safety Culture With System Thinking as Intervening Variabel - Septianto Halim, Intan Silviana Mustikawati, Rokiah Kusumapradja. (CV. Bunda Ratu, 2023)
Patient safety is currently a global concern in health services. The provision of high-quality essential health services depends on patient safety. The goal of patient safety is to establish a culture of safety in the hospital, increase the level of accountability the hospital has to patients and the public, reduce the number of incidents that occur in the hospital, and implement prevention programs to stop incidents from happening again. This study aims to determine the factors related to the application of patient safety culture, especially in the influence of competence, burn out on patient safety culture with system thinking as an intervening variable at Karya Medika I Hospital located in West Java. This research was conducted at Karya Medika I Hospital, with research time from October 2022 to March 2023, involving 87 functional nurses from treatment rooms to polyclinics, with data collection methods in the form of questionnaires about patient safety culture, competence, burn out and system thinking and using SPSS as statistical tools in processing the research data. For the result data; The Pearson test results obtained p value of 0.005 where the value is significant if the p value <0.05 this means that there is a relationship between competence and patient safety culture. In this study, it was found that the relationship between Competence and Burn Out variables had an effect on Patient Safety Culture through the intervening system thinking variable and this research was also in accordance with previous studies. It can be seen in this study that there is a correlation between effective communication between medical personnel, the level of work fatigue and communication within the unit when there is a problem regarding patient safety culture through identifying patterns of thinking systems from nurses.